Long-Term Exposure to Ambient PM2.5, Sunlight, and Obesity: A Nationwide Study in China - Chen, Rui; Yang, Chao; Li, Pengfei; Wang, Jinwei; Liang, Ze; Wang, Wanzhou; Wang, Yueyao; Liang, Chenyu; Meng, Ruogu; Wang, Huai-yu; Peng, Suyuan; Sun, Xiaoyu; et al. (Frontiers in Endocrinology, 2022)
Background: Accumulated researches revealed that both fine particulate matter (PM2.5) and sunlight exposure may be a risk factor for obesity, while researches regarding the potential effect modification by sunlight exposure on the relationship between PM2.5 and obesity are limited. We aim to investigate whether the effect of PM2.5 on obesity is affected by sunlight exposure among the general population in China. Methods: A sample of 47,204 adults in China was included. Obesity and abdominal obesity were assessed based on body mass index, waist circumference and waist-to-hip ratio, respectively. The five-year exposure to PM2.5 and sunlight were accessed using the multi-source satellite products and a geochemical transport model. The relationship between PM2.5, sunshine duration, and the obesity or abdominal obesity risk was evaluated using the general additive model. Results: The proportion of obesity and abdominal obesity was 12.6% and 26.8%, respectively. Levels of long-term PM2.5 ranged from 13.2 to 72.1 μg /m3 with the mean of 46.6 μg /m3. Each 10 μg/m3 rise in PM2.5 was related to a higher obesity risk (OR 1.12 [95% CI 1.09-1.14]) and abdominal obesity (OR 1.10 [95% CI 1.07-1.13]). The association between PM2.5 and obesity varied according to sunshine duration, with the highest ORs of 1.56 (95% CI 1.28-1.91) for obesity and 1.66 (95% CI 1.34-2.07) for abdominal obesity in the bottom quartile of sunlight exposure (3.21-5.34 hours/day). Conclusion: Long-term PM2.5 effect on obesity risk among the general Chinese population are influenced by sunlight exposure. More attention might be paid to reduce the adverse impacts of exposure to air pollution under short sunshine duration conditions.